Collisional evolution of the trans-Neptunian region in an early dynamical instability scenario. Issue 4 (13th June 2022) - Benavidez, Paula G; Campo Bagatin, Adriano; Curry, Jacob; Álvarez-Candal, Álvaro; Vincent, Jean-Baptiste
ABSTRACT: Any early or late dynamical instability in the outer Solar system should have left their footprint on the trans-Neptunian object (TNO) populations. Here, we study the collisional and dynamical evolution of such populations numerically by an updated version of ALICANDEP, which suitably takes into account the onset of an early dynamical instability. Key parameters for collisional and dynamical evolution are chosen to match results with current observables. The new model (ALICANDEP-22) considers an original region located between 22 and 30 au, containing 20–30 M⊕ from which bodies are either dynamically ejected from the region or implanted into the current plutinos and hot classical trans-Neptunian belt. An in situ population of objects is also present since the beginning, corresponding to the current cold-classical population. Collisional and dynamical evolution is allowed starting from initial conditions accounting for streaming instability models and observational constraints. ALICANDEP-22 successfully reproduces observational constraints as well as the shape of the size-frequency distribution expected for the Trojan population. The model concludes that Arrokoth is likely a primordial body but cannot be conclusive on the origin of comet 67P/Churyumov–Gerasimenko. The current presence of bodies larger than Pluto in the outer TNO population – waiting to be discovered – is compatible with the initial distributions that allow the model to match current constraints.